Development and Characterization of Paclitaxel-Loaded Magnetic Nanoparticle-Embedded Transdermal Patches for Non-Invasive Breast Cancer Therapy - Sreeharsha, Nagaraja; Nagaraj, Shobana; Naveen, Nimbagal Raghavendra; Raikar, Prasidhhi; Goudanavar, Prakash; Meravanige, Girish; Shiroorka, Predeepkumar Narayanappa; Swaroop, Krishna (Indian Journal of Pharmaceutical Education and Research, 2025)
Background Breast cancer remains a significant health concern, necessitating the development of advanced drug delivery systems for improved therapeutic outcomes. This study focuses on the design and evaluation of non-invasive transdermal patches incorporating magnetic nanoparticles (MNPs) for targeted Paclitaxel (PTX) delivery. Materials and Methods PTX-loaded MNPs were synthesized and characterized for particle size, zeta potential, drug loading capacity, and stability. The nanoparticles were embedded into transdermal patches formulated using Hydroxypropyl Methylcellulose (HPMC), ethyl cellulose (EC), polyethylene glycol 100 (PEG 100), and menthol to enhance permeation and provide controlled drug release. Physicochemical evaluations, in vitro drug diffusion studies using a Franz diffusion cell, and stability assessments were conducted. The release kinetics of the optimized formulation were analyzed to determine the drug release mechanism. Results The optimized PTX-MNP-loaded transdermal patch exhibited an entrapment efficiency of 96.83% and demonstrated prolonged drug release, following a non-Fickian (anomalous) transport mechanism, suggesting a combination of diffusion and polymer relaxation. Ex vivo permeation and stability studies confirmed the formulation’s efficiency and biocompatibility. Conclusion The developed PTX-MNP-loaded transdermal patch presents a promising non-invasive alternative for breast cancer therapy. Its sustained drug release profile, enhanced permeation, and biocompatibility make it a potential candidate for future clinical applications in targeted cancer treatment.
Keywords: Breast Cancer; Magnetic Nanoparticles; Paclitaxel; Transdermal Patches.